Implemetasi Konsep Adiwiyata dalam Pembelajaran Fisika SMAN 10 Bulukumba - Hasan, A. Eka Fitrianti; Suarti, Suarti; Hasanah, Ummul (Al-Khazini: Jurnal Pendidikan Fisika, 2021)
The  Adiwiyata  program  is  a  program  prepared  by  the  government  in  the world of education and creates responsible school citizens in environmental management  efforts.  SMA  Negeri  10  Bulukumba  is  a  school  that  has implemented the Adiwiyata program. The objectives of this study are: 1) To determine  the  implementation  of  curriculum  policies  related  to  the  concept of  adiwiyata  in  physical  learning  2)  To  determine  the  implementation  of teachers in the integrated physics learning process the concept of adiwiyata. 3)To  find  out  the  behavior  of  students  in  learning  physics  with  the integration  of  the  concept  of  adiwiyat.  This  research   is  a  descriptive qualitative   research   with   ethnographic   method.   Collecting   data   using interviews,  observation  documentation,  triangulation.  The  data  analysis technique used  in this study was done  by analyzing domain and taxonomy results showed that the Adiwiyata curriculum policy in physics learning refers  to  educational  programs,  such  as  graduation  competency  standards, content  standards,  process  standards,  educators  and  education  personnel standards,  facilities  and  infrastructure  standards,  management  standards, education   financing   standards,   educational   assessment   standards.   The implementation of physics  subjects with environmentalinsight  is  integrated into physics subjects through  learning activities  in the classroomis  seen  by solving  environmental  problems  using  the  concept  of  physicsand  outside the classroom is carried out by utilizing the school environment as a physics learning laboratory. But not all physical materials can be integrated with the environment  but  only  certain  materials.  Student  behavior  in  Adiwiyata learning  is  seen  from  student  learning  to  have  an  attitude  of  caring  for  the environment  and  changing  student  habits  by  instilling  character  values to protect the surrounding environment.